Mediating effects of attitude on the relationship between knowledge and willingness to organ donation among nursing students - Chen, Xiaohang; Zhou, Xin; Xu, Yan; Pan, Li; Li, Peizheng; Liang, Wenjin; Jin, Lv; Zhang, Chunhua; He, Chongxiang (Frontiers in Public Health, 2024)
The current rate of organ donation in China falls significantly below the global average and the actual demand. nursing students play a crucial role in supporting and promoting social and public welfare activities. This study primary aims to analyze the levels of knowledge, attitudes, willingness toward organ donation, and attitudes toward death among nursing students, and investigate the mediating role of attitude in the relationship between knowledge and willingness. The secondary aims to identify factors that may influence the willingness.Methods: A convenience sample of nursing students completed online-administered questionnaires measuring the level of knowledge, attitudes, and willingness toward organ donation before and after clinical internship. Spearman correlation and mediation analyses were used for data analyses.Results: Before the clinical internship, there were 435 nursing students who had not yet obtained their degrees and were completing their clinical internships. After the internship, this number decreased to 323. The mean score for knowledge before and after the clinical internship ( 7.17 before and 7.22 after, with no significant difference), the attitude (4.58 before and 4.36 after, with significant difference), the willingness (12.41% before and 8.67% after, with significant difference), the Death Attitude Profile-Revised (DAP-R) score (94.41 before and 92.56 after, with significant difference). The knowledge indirectly affected nursing students' willingness to organ donation through attitude. Knowledge had a direct and positive impact on attitudes (β=1.564). Additionally, nursing students' attitudes positively affected their willingness (β=0.023). Attitudes played a mediating role in the relationship between knowledge and willingness (β=0.035). Additionally, attitude towards death, fear of death, and acceptance of the concept of escape were found to be correlated with their willingness.Organ donation willingness was found to be low among nursing students. Positive attitudes were identified as a mediating factor between knowledge and willingness. Additionally, DAP-R was a related factor. Therefore, it is recommended to focus on improving knowledge and attitude, as well as providing death education to help nursing students establish a positive attitude toward death.These efforts can contribute to the promotion of organ donation.